Gute Betreuung im Alter in der Schweiz - Knöpfel, Carlo (Seismo, 2018)
Apart from financing retirement provision, assistance and care for elderly people ist he central issue in Swiss politics concerning elderly people. While medical care has been in focus of the discourse about health and social politics for a while, the issue of care work was often only touched upon. This book discusses legal issues concerning medical care and care work, describes the involved actors, the education, the recruitment and the wages of employees. Furthermore, self-sustained and health promoting living at a high age is an issue. It becomes evident that care work is neither legally defined nor with regards to content. Legal regulations securing quality standards, legal stability for employees as well as the integration of care work into the system of social security, are lacking in practice. In view of these conditions and changes and society, this book shows that the issue of care work needs more consideration in the political discourse concerning elderly people.